2010
DOI: 10.1088/1674-1056/19/6/064213
|View full text |Cite
|
Sign up to set email alerts
|

Study of second-order nonlinear hyperpolarisability of all-trans-β-carotene in solutions by linear spectroscopic technique

Abstract: This paper demonstrates the second-order nonlinear hyperpolarisability γ of all-trans-β-carotene in different solvents by linear spectroscopic technique that is based on resonance Raman scattering and UV–VIS (Ultraviolet-visible) absorption spectroscopy. Owing to the two-level model well describing the link that exists between the resonance Raman scattering and stimulated Raman scattering, the stimulated Raman polarisability αR can be calculated through the two-photon resonance system. The value of γ of all-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It was shown in [11] that, under picosecond laser excitation with a wavelength of 532 nm, two Stokes and one anti-Stokes components are observed in the SRS. In [12][13][14][15], SRS was studied in ethanol microdroplets with the addition of Rhodamine 6G. It is shown that the laser generation of Rhodamine 6G is partially compressed due to SRS in ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in [11] that, under picosecond laser excitation with a wavelength of 532 nm, two Stokes and one anti-Stokes components are observed in the SRS. In [12][13][14][15], SRS was studied in ethanol microdroplets with the addition of Rhodamine 6G. It is shown that the laser generation of Rhodamine 6G is partially compressed due to SRS in ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…Many organic thin films have been fabricated and their physical properties have been examined in order to develop fine nonlinear optical devices. Carotenoids, although due to their poor structural stability, can be a good model to investigate because of their large nonlinear optical susceptibilities [9][10][11][12]. Different types of β-Car thin-films were fabricated, and their optical absorption and resonance Raman spectroscopy were examined.…”
Section: Introductionmentioning
confidence: 99%